Optimalization of the Ferronickel Production Process through Improving Desulfurization Effectiveness - Izet Ibrahimi; Nurten Deva; Sabri Mehmeti (Salehan Institute of Higher Education, 2020)
Desulphurization of Ferronickel in the converters with oxygen is the most complex part of the technological process in the Drenas foundry. Sulphur in the ferronickel melting is mostly in the form of FeS, with a melting temperature of 1195oC, and it has tendency to dissolve indefinitely in liquid iron. Our objective is to determine the sulphur removal coefficient, as a key indicator of the desulphurization efficiency in the converter, by measuring the activity and concentration of sulphur and other elements in liquid Fe and melting. Determination of this coefficient is done according to the analytical method, while comparing the current process parameters with those of the new desulfurization methods, other indicators of the refining process are determined. The refining process and the effective conduct of the study depend on the XRD analysis database of metal and slag, and as well of the technological refining process analysis data. Research has shown that desulfurization efficiency is a function of the sulphur removal coefficient, respectively; metal composition, slag, oxygen activity, CaO/SiO2 ratio, sulphide capacity, fluidity, surface pressure, etc.). In addition to this coefficient, other indicators of refining process optimization are defined.